Behavioral Couples Therapy untuk memperbaiki pola komunikasi pada pasangan suami istri - Noventia Sekar Pratiwi (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
The family is the smallest unit of society that lives under one roof and is interdependent physically, psychologically and socially. In the family there are problems that can develop from the relationship between husband and wife. One of the problems that often arise in husband-wife relationships is communication patterns that hurt each other.Negative communication patterns that are repeated in everyday life form a person's assessment of others to become increasingly negative. If the negative communication pattern is maintained, the more severe the problems will be faced so that it can affect marital satisfaction in the household. Subjects are husband and wife who have problems with negative communication patterns. Data was collected using interviews, observations and the ENRICH marital satisfaction scale. Problems with negative communication patterns can be corrected with behavioral couples therapy (BCT).Interventions were carried out to improve communication patterns that were originally aversive and hurt each other to become more positive, thereby increasing marital satisfaction. BCT consists of 6 sessions. The results of the intervention show that the problem of negative communication patterns can be overcome effectively using behavioral couple therapy. Communication skills improve negative communication in partners. While the behavior exchange technique is effective in overcoming problems in interaction.